CalcPEFDairy: A Product Environmental Footprint compliant tool for a tailored assessment of raw milk and dairy products. (15th April 2020) - Egas, D.; Ponsá, S.; Colon, J.
Abstract: A compliant tool (CalcPEFDairy ) to determine the Product Environmental Footprint (PEF) of Dairy products has been developed following the Product Environmental Footprint Category Rules (PEFCR) v.6.3 guidance and the 2018 approved PEFCR for Dairy products. CalcPEFDairy is a new tool that simplifies and reduces the work for LCA practitioners when implementing the PEFCR for Dairy products. On contrary to traditional LCA software, CalcPEFDairy includes all the emission models needed to calculate farm and crop cultivation direct emissions and it also implements the specific calculation formulas stated in the PEFCR such as the Circular Footprint and Data Quality Requirement formulas. Moreover, the PEF compliant datasets provided by the Life Cycle Data Network are incorporated in the tool as source of secondary data. To demonstrate the accuracy of the tool a traditional dairy farm in Catalonia (Northwest of Spain) was assessed and the results compared with the European representative PEF compliant datasets for the production of raw milk, cheese and yoghurt. In addition to the environmental profile, CalcPEFDairy has determined the case study's environmental single score (ESS) for the production of raw milk (1.0 × 10 −4 ) cheese (9.7 × 10 −6 ) and yoghurt (1.4 × 10 −5 ); these ESS results are within the range of the ESS obtained from the analysed EF-datasets. The data sets' average ESS for raw milk is 9.9 × 10 −5 ± 1.1 × 10 −5, while for cheese and yoghurt are 1.5 × 10 −5 ± 3.1 × 10 −6 and 1.9 × 10 −5 ± 3.4 × 10 −6 respectively. A 78% of the raw milk production ESS is attributed to the dairy farm activities while, the raw milk production stage affects in a 87.4% and 80.1% to the ESS for cheese and yoghurt respectively. Graphical abstract: Image 1 Highlights: Incorporation of the official PEF datasets for background processes. Build in PEF compliant dairy farm emission models and calculation parameters. Directly comparable results: 16 impact categories and environmental single score. Data Quality Requirement calculator for a PEF complaint study. Incorporation of the Circular footprint formula for end of life assessment.